Implementation of the regional program of cervical cancer screening by liquid-based cytology in the Rostov region - Т. A. Dimitriadi; D. V. Burtsev; E. A. Dzhenkova (Исследования и практика в медицине)
Purpose of the study. To evaluate  the effectiveness  of the regional  cervical cancer screening  program by (LB) liquid‑based cytology.Materials and methods. The geography of screening includes 54 medical units of the Rostov region, where patients are taken swabs from the cervix. HPV positive patients with abnormal PAP smears are invited to the Regional cervical pathology  center (RCPC) for diagnosis and treatment.  LB cytology, the HPV test RealTime PCR, colposcopy  with video recording, biopsy of the cervix by the method of loop excision or electroradiographic conization.Results. From 2014 to 2017, 188 641 cytology tests were performed. Cervical cancer was revealed in 189 women — (0.1%), H‑SIL and ASCH in 566 (0.3%), 377 ASCUS (0.2%), L‑SIL in 23014 (12.2%), absence of intracellular lesions or malignancy (NILM) in 164495 (87.2%). 2162 HPV — positive women aged 18 to 69 years were invited to the RCPC gynecologist for examination.  Treatment  by conization  (622) and excision  (830) of the cervix was performed  in 1452 patients,  H‑SIL and CIS were revealed in 1162 women (78%).Conclusion. tests such as LB cytology and HPV testing, their optimal multiplicity and sequence allow timely detection and treatment of precancerous cervical epithelium lesions.